Students’ Perception of Webtoon as a Self-Directed Learning Medium for Reading Skill - As Sabiq, Agus Husein; Rohmatulhaq, Naf'an (Indonesian Journal Publisher, 2024)
This research aims to describe Students' Perception of Webtoon as a Self-Directed Learning Medium for Reading Skills. Further investigation into this issue was required because Webtoon is considered a medium that enhances students' reading skills. This research uses mixed methods, with questionnaires as the main instrument and interviews as support. The object of this research was Webtoon for English learning medium. Through 16 questionnaire items distributed to 48 students, the research found a mean of 76% from 4 indicators: English learning motivation, students’ reading interest, self-directed learning medium, and students' reading skills. This research found that students believe Webtoon could enhance their English learning motivation and reading interest. Furthermore, students believe that the efficacy and accessibility of Webtoon make it an appropriate medium for learning English independently. Although students encounter certain challenges, it does not reduce the value of Webtoon as a medium for learning English because they feel a positive influence on their reading skills. As a result, students believe Webtoon was not only a fun activity but could also serve as a suitable medium for learning English.